Optically Transparent Anionic Nanofibrillar Cellulose Is Cytocompatible with Human Adipose Tissue-Derived Stem Cells and Allows Simple Imaging in 3D - Jonathan J. Sheard; Mesude Bicer; Yiming Meng; Alessia Frigo; Rocío Martínez Aguilar; Thomas M. Vallance; Donata Iandolo; Darius Widera (Stem Cells International)
The anti-inflammatory and immunomodulatory properties of human mesenchymal stromal cells (MSCs) are a focus within regenerative medicine. However, 2D cultivation of MSCs for extended periods results in abnormal cell polarity, chromosomal changes, reduction in viability, and altered differentiation potential. As an alternative, various 3D hydrogels have been developed which mimic the endogenous niche of MSCs. Nevertheless, imaging cells embedded within 3D hydrogels often suffers from low signal-to-noise ratios which can be at least partly attributed to the high light absorbance and light scattering of the hydrogels in the visible light spectrum. In this study, human adipose tissue-derived MSCs (ADSCs) are cultivated within an anionic nanofibrillar cellulose (aNFC) hydrogel. It is demonstrated that aNFC forms nanofibres arranged as a porous network with low light absorbance in the visible spectrum. Moreover, it is shown that aNFC is cytocompatible, allowing for MSC proliferation, maintaining cell viability and multilineage differentiation potential. Finally, aNFC is compatible with scanning electron microscopy (SEM) and light microscopy including the application of conventional dyes, fluorescent probes, indirect immunocytochemistry, and calcium imaging. Overall, the results indicate that aNFC represents a promising 3D material for the expansion of MSCs whilst allowing detailed examination of cell morphology and cellular behaviour.